Krisis Metodologis Maqasid al-Shari’ah: : Studi Perbandingan Pemikiran al-Syatibi dengan Jasser Auda - Sulthon, Mohammad (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2025)
The dynamics of society continue to develop, legal problems thus always accompany it in line with the development of culture, science and technology. The actions of some faqih in responding to contemporary dynamics are often only defensive-apologetic in nature, not solution-oriented and even counterproductive. Actually, the fuqaha are not not doing ujtihad at all, they have done it, but limited to repeated readings of the results of previous ijtihad. And actually what needs to be reconstructed is not Islamic law, but the means of making Islamic law, namely ushul fiqh, in this case maqashid sharia. In the classical era, there was already a theory about maqashid sharia, but it was considered inadequate in terms of methodology. From that the author makes a conclusion about how the thinking of Asy-Syatibi and Jasser Auda in the maqashid syariah? This study uses a qualitative approach. The results show that asy-Syatibi has transformed the maqashid syariah by releasing the maqasid from the material of law to the principles of law, changing the wisdom from behind the rules to the basis of the rules, and induction to the verses of the Qur'an. While the maqashid offered by Jasser Auda is an approach to Islamic philosophy that accumulates in; the cognitive character of the system, the whole system, openness, hierarchical interplay, multidimensionality, and intentionality